Relationship between a Public Float and the Firm’s Cash Holdings - Truong, Hoang Mai Ha; 이은서; 이준엽; Leach, Megan (경영교육연구, 2021)
[Purpose]This study examines the relationship between a public float and the firm’s cash holdings. [Methodology]Public float is defined as the market value of all common equity held by non－affiliates. Following Harford et al. (2008), we use three measurements for cash holdings: cash divided by total assets minus cash, log of cash divided by sales, and industry adjusted cash divided by total sales. [Findings]Using a sample of U.S. IPO from 1990 to 2015, this study shows that the relationship between a public float and the firm’s cash holdings is negative and significant, supporting the pecking order theory. [Implications]According to Meles and Salerno (2020), to determine how many stock shares would be public float is one of the most important strategic decision for insiders who are planning an IPO. Our study contributes to the cash holdings literature by showing the relationship between a public float and the firm’s cash holdings.
Keywords: 부동주; 현금 보유수준; Public Float; Cash Holdings